1921 Ga. Laws 248 - (:unkn) unknown (My University, 1921)
Explosives, Use of Regulated, § 1: Prohibited the possession of any dynamite, nitro-glycerine, gun cotton, any other high explosive without registering with the Explosive Register.
Keywords: POSSESSION - NON-GUN ARMS